Application of acid tolerant Pedioccocus strains for increasing the sustainability of lactic acid production from cheese whey. (October 2016) - Juodeikiene, Grazina; Zadeike, Daiva; Bartkiene, Elena; Klupsaite, Dovile
Abstract: The major challenge within the presented study is the possibility to increase the effectiveness of fermentative lactic acid production. Four acid tolerant Pedioccocus spp. strains, previously isolated from sourdough medium, were screened for their ability to produce the enantioselective lactic acid (LA) from cheese whey and compared to the traditional in dairy technology Lactobacillus delbrüeckii spp. bulgaricus . The effects of lactose hydrolysis by using commercial β-galactosidase from Aspergillus oryzae and acid neutralization on fermentation performance and LA stereoisomer ratio were investigated. The Pediococcus pentosaceus strains were indicated as the DL-forming lactic acid bacteria, in which the percentage of thel (+)-lactic acid is high (75% from the total LA), while Pediococcus acidilactici and Lactobacillus bulgaricus produced L(+) and D(−) lactic acid, respectively. The L/D ratio could be increased by using enzyme hydrolysed whey for fermentation; however, prolonged fermentation induced the formation ofd (−)-lactic acid. Experiment revealed the different tolerance of tested LAB to acid medium, thus required the different amounts of neutralizing agent. The maximum production ofl (+)-lactic acid up to 47.0–51.2 g/L from hydrolysed whey was acquired in a pH 4.4–4.5 by P. acidilactici KTU05-7 and P. pentosaceus KTU05-9 using 2% (w/v) of CaCO3, while the use of L. bulgaricus required a threefold higher amount of the neutralizing agent. Highlights: Enantioselective LA production from whey by low acid tolerant LAB has been analyzed. The D(−)/L(+) ratio depended on LAB strain used for whey fermentation. The maximum production of LA from hydrolysed whey was achieved at a pH 4.4–4.5. Prolonged fermentation induced the formation of D(−) lactic acid. The sustainability of fermentative lactic acid production has been increased.